Three-Step Iterative Method with Fifth Order Convergence for Solving Non-linear Equations - Kumar Palli, Rajesh; Sandeep Kumar Mylapalli, Mani; Sri , Ramadevi (International Journal of Psychosocial Rehabilitation, 2020)
In this paper, a new three-step iterative method is proposed based on Newton’s Method to obtain the numerical solution of a non-linear equation. We prove that our method takes over fifth-order convergence, and the efficiency of the recommended method is shown by the numerical examples comparing it with existing methods.